A Comparative-Correlational Study Of Attitudes Toward And Motivation For Learning English As A Foreign Language In Grade 9 Students From Akha, Bamar And Shan Ethnic Groups At № 2 Basic Education High School, Keng Tung, Eastern Shan State, Myanmar - Thant, Zaw Myo; González, Orlando Rafael González (Scholar: Human Sciences, 2019)
The purpose of this study was to determine whether there was a significant relationship between attitudes and motivation of Grade 9 students toward English as a foreign language from the Akha, Bamar, and Shan ethnic groups and to compare both variables among three different ethnic groups at № 2 Basic Education High School, Keng Tung, Eastern Shan State, Myanmar. A total of 199 students participated, and the instrument adapted for this study was the latest version of Gardner’s (2004) Attitude/Motivation Test Battery. Pearson product-moment correlation coefficient was used to examine the relationship between the research variables, and a one-way analysis of variance (ANOVA) was performed to determine if there were significant differences between attitudes and motivation of the participant students. From this study, a positive attitude and high motivation of Grade 9 students toward learning English as a foreign language (EFL) were found, regardless of their ethnic memberships. Also, it was found a statistically strong, positive correlation between attitudes toward and motivation for learning EFL of Grade 9 students in each ethnic group. Furthermore, the findings also revealed a significant difference between attitudes toward EFL of the students, but no significant difference between motivations for learning EFL of the students in all three ethnic groups. Finally, recommendations for teachers, students, administrators and future researchers are presented.